2021
DOI: 10.1097/mnh.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Advances in management of hepatorenal syndrome

Abstract: Purpose of reviewHepatorenal syndrome (HRS) is encountered frequently in patients with end-stage liver disease and remains an important cause of morbidity and mortality in this patient population. This review will focus and provide updates on pathophysiology, assessment of kidney function, new definitions, and treatment and prevention of HRS.Recent findingsPathophysiology of HRS has been elucidated more recently and in addition to hemodynamic changes, the role of systemic inflammatory response contributes sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In 2007-2008, multiple randomized control trials on terlipressin were published and have influenced the medical management HRS as well as patient outcomes[ 9 - 11 , 14 , 15 ]. Studies have shown potential beneficial effects of terlipressin, a potent selective splanchnic and extrarenal vasoconstrictor, on kidney function among patients with HRS[ 10 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007-2008, multiple randomized control trials on terlipressin were published and have influenced the medical management HRS as well as patient outcomes[ 9 - 11 , 14 , 15 ]. Studies have shown potential beneficial effects of terlipressin, a potent selective splanchnic and extrarenal vasoconstrictor, on kidney function among patients with HRS[ 10 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, 60 patients with hepatorenal syndrome were given midodrine, octreotide, and albumin, while 21 received only albumin. Midodrine and octreotide therapy were associated with significantly lower mortality (43 versus 71 percent) and a considerably higher proportion of patients with hepatorenal syndrome resolution (40 versus 10 percent) [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Because of the increased production of vasodilator factors in the advanced phase, vasodilation is more prominent and cannot be countered by an increase in cardiac output. Decreased cardiac output appears to come first in severe cirrhosis with ascites, and then hepatorenal syndrome develops [3,17,[28][29][30][31].…”
Section: Pathophysiology Of Hepatorenal Syndrome and Biomarkersmentioning
confidence: 99%